2021
DOI: 10.1007/s10854-020-05217-2
|View full text |Cite
|
Sign up to set email alerts
|

Wearable temperature sensor for human body temperature detection

Abstract: This paper presents the production and the characterization of the multi-walled carbon nanotube (MWCNT) printed flexible temperature sensors for high-precision reading in temperature sensing applications. The temperature sensor was fabricated using the inkjet printing method by depositing carbon nanotube (CNT) ink on soft taffeta fabric. An aqueous CNT-based conductive ink was formulated for the inkjet printing process. A translucent polyurethane (PU) welding tape was used as an encapsulation layer on the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Inkjet printing can be used to devise wearable temperature sensors. Kuzubasoglu et al [261] jetted an aqueous carbon nanotube (CNT) conductive ink to fabricate a wearable temperature sensor. Vuorinen et al [262] demonstrated a temperature sensor by printing graphene/Poly (3,4-ethylenedioxythiophene):poly (styrenesulfonate) (PEDOT:PSS) ink on a skin-conformable polyurethane substrate.…”
Section: Wearable Flexible and Stretchable Devicesmentioning
confidence: 99%
“…Inkjet printing can be used to devise wearable temperature sensors. Kuzubasoglu et al [261] jetted an aqueous carbon nanotube (CNT) conductive ink to fabricate a wearable temperature sensor. Vuorinen et al [262] demonstrated a temperature sensor by printing graphene/Poly (3,4-ethylenedioxythiophene):poly (styrenesulfonate) (PEDOT:PSS) ink on a skin-conformable polyurethane substrate.…”
Section: Wearable Flexible and Stretchable Devicesmentioning
confidence: 99%
“…Also, studies and initiatives are constantly developing wearable technologies to monitor skin temperature. In general, such strategies apply skin carbon nanotube (CNT) printed adhesives that provide more precise temperature detection [20,21]. However, CNT-based sensors require a computing unit to acquire data from the sensors to make them available for processing.…”
Section: Temperaturementioning
confidence: 99%
“…In previous studies, most wearable sensors have focused more on the connection with smart devices. They mainly integrate various data in real-time through technical means and presents human physical parameters such as heart rate [23], blood oxygen saturation [24], exercise steps [25], breathing rate [26], blood pressure [27], and body temperature [28]. However, these types of physical monitoring may not fully meet the molecular level requirements of various human health monitoring because they cannot provide the characteristics of related diseases early and establish prevention models.…”
Section: Introductionmentioning
confidence: 99%